PKM SESSION OF THE OSENG LANGUAGE COMMISSION 577 VOCABULARY OF EAST JAVA HALL - Agus Mursidi (MAN Insan Cendekia Jambi, 2022)
In the draft result of the Oseng vocabulary inventory that has been carried out by the Koord Team. KKLP of Dictionary and Terminology, and Coords. KKLP for the Protection and Modernization of the East Java Language Center. The number of words generated from the field is 730 words that must be verified and 577 words are verified. The feasibility of a verified word is very decisive to be submitted in the session of the word validation commission of the East Java Language Center of the Ministry of Education and Culture of Indonesia for final verification by presenting resource persons from the Central KKLP represented by Dr. Adi Budiwiyanto and Amat Triatna, SS There was a request from the Chair of the East Java Province Language Center at the Faculty of Teacher Training and Education, PGRI Banyuwangi University to become a resource person in the 577-word Oseng Vocabulary Verification Session as a continuation of the 730-word Vocabulary Workshop, namely Dr. Agus Mursidi, M.Pd. Apart from UNIBA, there are also Oseng customer representatives, namely from the Minhajul Qowwim Oseng Language Research Institute, SS. From DBK. 5 people from the Coord Team. KKLP of Dictionary and Terminology, Researcher with the chairman of Puspa Ruriana, M.Hum, members of Adista Nur Primantari, MA and Yuyun Kartini, SS and 2 language instructors. The activity was carried out in 5 days at the Luminor hotel from 4-8 July 2022 with a letter of assignment starting 4-9 July 2022. From the results of the verification carried out by the Team, 5% of words were deleted because they were already in the big Indonesian dictionary, 5% of repeated words, 10% of words that must be verified by vocabulary sources, 80% (402) of verified words that are eligible to be submitted for data entry to the Big Indonesian Dictionary submitted by the Indonesian Language Center of the Ministry of Education and Culture.